Effect of lactobacillus reuteri-derived probiotic nano-formulation on recurrent aphthous stomatitis: a double-blinded randomized clinical trial - Nazafarin Samiraninezhad; Hojat Kazemi; Mostafa Rezaee; Ahmad Gholami (BMC, 2023)
Abstract Objectives We aimed to assess the therapeutic effects of a topical probiotic nano-formulation derived from Lactobacillus reuteri on treating recurrent aphthous stomatitis. Materials and methods 60 participants were randomly allocated into two groups (control and probiotic). Probiotic group administered topical probiotic nano-formulation three times a day for seven days. The control group administered a standard analgesic oral rinse. The size of ulcer(s) and pain severity were recorded on days 0, 3, 5, and 7 after intervention. Results Before the intervention, the groups had no significant differences in terms of pain severity (P-value = 0.28) and lesion size (P-value = 0.24). Both groups exhibited significant reductions in pain severity and lesion size over the course of the intervention. After one week, the probiotic group had a notably larger lesion size reduction than the control group (P-value = 0.01). The probiotic group also showed a significantly greater reduction in pain severity than the control group (P-value = 0.04). Conclusions Applying topical probiotic nano-formulation derived from Lactobacillus reuteri three times a day decreased lesion size and pain severity in RAS patients faster than the local analgesic oral rinse. Clinical relevance Lactobacillus reuteri-derived probiotic nano-formulation might be a promising treatment option for RAS.